Synthesis and Spectroscopic Properties of [VO(aspa/gluta)H2O] and [VO(aspa/gluta)ImH] - Singh, P.K. (Asian Journal of Chemistry, 2016)
Reaction of the tridentate amino acids, viz., aspartic acid and glutamic acid with VO2+ ion in 1 : 1 molar ratio in aqueous solution yields [VO(aspa/gluta)H2O], (dimeric), while reaction with VO2+ ion, amino acid and imidazole in 1 : 1 : 1 molar ratio in aqueous solution yields [VO(aspa/gluta)ImH], (monomer). In addition to synthesis, we report the magnetic IR, EPR and optical absorption data of these compounds.